4
$\begingroup$

Question

I would like to know the simplest way to find the volume of the solid of revolution created by rotating the parabola $y=x^2$ around the line $y=x$ (the shape shown in blue below). I am currently taking AP BC Calculus as a junior in high school, so a method that uses those concepts would be ideal, but if it is far simpler to use some higher math, I will look into it :)

enter image description here

The following is what I have tried using a variation of the disk method. I believe that is correct, but, as the reader can see, it is very complex.

My Method

To employ the disk method, first, derive a function for the radius of the solid as a function of $x$ along $y=x$. Then, square it and multiply by $\pi$. Lastly, integrate on the interval $[0,\sqrt{2}]$.

Begin by constructing a line perpendicular to $y=x$ that intersects $y=x$ (occationally $f(x)$) and $y=x^2$ (occationally $g(x)$) at $(x_2,y_2)$ and $(x_1,y_1)$, respectively (as shown below).

enter image description here

$$d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\tag{1}$$ Use the distance formula to find the distance between these points.

$$\begin{align} \color{gray}{y} &\color{gray}{=} \color{gray}{-x+2x_2}\\ y &=x \end{align}$$ $$x=-x+2x_2$$ $$2x=2x_2$$ $$x_2=x\tag{2}$$


$$\begin{align} y_2&=f(x_2)\\ &=x\tag{3} \end{align}$$


$$\begin{align} \color{gray}{y} &\color{gray}{=} \color{gray}{-x_1+2x_2}\\ \color{gray}{y} &\color{gray}{=} \color{gray}{-x_1+2x}\\ y &={x_1}^2 \end{align}$$ $${x_1}^2=-x_1+2x$$ $$0=1{x_1}^2+1x_1+-2x$$ $$\begin{align} x_1&=\frac{-1+\sqrt{1^2-4(1)(-2x)}}{2(1)}\\ &=\frac{\sqrt{1+8x}-1}{2}\tag{4} \end{align}$$


$$\begin{align} y_1&=g(x_1)\\ &=\bigg(\frac{\sqrt{1+8x}-1}{2}\bigg)^2\tag{5} \end{align}$$ Find the variables in the distance formula as functions of $x$ (Eqns. 2-5 with derivations listed above them, respectively).

$$\begin{align} d&=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ &=\sqrt{\Bigg(x-\frac{\sqrt{1+8x}-1}{2}\Bigg)^2+\Bigg(x-\bigg(\frac{\sqrt{1+8x}-1}{2}\bigg)^2\Bigg)^2}\tag{6} \end{align}$$

Plug Eqns. 2-5 into the distance formula.

$$\begin{align} d&=\sqrt{\Bigg(x-\frac{\sqrt{1+8x}-1}{2}\Bigg)^2+\Bigg(x-\bigg(\frac{\sqrt{1+8x}-1}{2}\bigg)^2\Bigg)^2}\\ &=\sqrt{\Bigg(x-\frac{\sqrt{1+8x}-1}{2}\Bigg)^2+\Bigg(x-\bigg(\frac{(1+8x)-2\sqrt{1+8x}+1}{4}\bigg)\Bigg)^2}\\ &=\sqrt{\Bigg(x-\frac{\sqrt{1+8x}-1}{2}\Bigg)^2+\Bigg(x-\bigg(\frac{2+8x-2\sqrt{1+8x}}{4}\bigg)\Bigg)^2}\\ &=\sqrt{\Bigg(\frac{2x}{2}-\frac{\sqrt{1+8x}-1}{2}\Bigg)^2+\Bigg(\frac{2x}{2}-\frac{1+4x-\sqrt{1+8x}}{2}\Bigg)^2}\\ &=\sqrt{\Bigg(\frac{2x-\sqrt{1+8x}+1}{2}\Bigg)^2+\Bigg(\frac{2x-1-4x+\sqrt{1+8x}}{2}\Bigg)^2}\\ &=\sqrt{\Bigg(\frac{1+2x-\sqrt{1+8x}}{2}\Bigg)^2+\Bigg(\frac{-1-2x+\sqrt{1+8x}}{2}\Bigg)^2}\\ &=\sqrt{2\Bigg(\frac{1+2x-\sqrt{1+8x}}{2}\Bigg)^2}\\ &=\sqrt{2\Bigg(\frac{1+4x^2+(1+8x)+4x-2\sqrt{1+8x}-4x\sqrt{1+8x}}{4}\Bigg)}\\ &=\sqrt{\frac{4x^2+12x-(4x+2)\sqrt{1+8x}+2}{2}}\\ &=\sqrt{2x^2+6x-(2x+1)\sqrt{1+8x}+1}\tag{7} \end{align}$$

Simplify Eqn. 6.

$$\begin{align} r&=\sqrt{2\bigg(\frac{x}{\sqrt{2}}\bigg)^2+6\bigg(\frac{x}{\sqrt{2}}\bigg)-\bigg(2\bigg(\frac{x}{\sqrt{2}}\bigg)+1\bigg)\sqrt{1+8\bigg(\frac{x}{\sqrt{2}}\bigg)}+1}\\ &=\sqrt{2\bigg(\frac{x^2}{2}\bigg)+6\bigg(\frac{\sqrt{2}x}{2}\bigg)-\bigg(2\bigg(\frac{\sqrt{2}x}{2}\bigg)+1\bigg)\sqrt{1+8\bigg(\frac{\sqrt{2}x}{2}\bigg)}+1}\\ &=\sqrt{x^2+3\sqrt{2}x-\big(\sqrt{2}x+1\big)\sqrt{1+4\sqrt{2}x}+1}\tag{8} \end{align}$$

Dilate Eqn. 7 by $\sqrt{2}$ in the x-direction to make the distance between the functions x-intercepts equal to the distance between the two intercepts of $f(x)$ and $g(x)$. Simplify to give Eqn. 8. Note that the graph of Eqn. 8 from $[0,\sqrt{2}]$ (below in green) compares to the reflection over the x-axis of the final equation for a parabola rotated 45 degrees given by Ennar (below in red), as it should.

enter image description here Graph from Desmos.

Integration by parts work (for below): $$\color{red}{\int\big(\sqrt{2}x+1\big)\sqrt{1+4\sqrt{2}x} \ dx}$$ $$ \begin{array}{|c|} \hline \mathbf{u=\sqrt{2}x+1},\ \mathbf{dv=\sqrt{1+4\sqrt{2}x} \ dx}\\ \hline \begin{array}{c|c} \frac{du}{dx}=\sqrt{2} & \int dv=\int\sqrt{1+4\sqrt{2}x}\ dx\\ \mathbf{du=\sqrt{2}\ dx} & v=\int\sqrt{w}\ \frac{dw}{4\sqrt{2}}\\ & v=\frac{1}{4\sqrt{2}}\int\sqrt{w}\ dw\\ & v=\frac{1}{4\sqrt{2}}\times\frac{w^\frac{3}{2}}{\frac{3}{2}}\\ & v=\frac{2}{12\sqrt{2}}w^\frac{3}{2}\\ & \mathbf{v=\frac{1}{6\sqrt{2}}\big(1+4\sqrt{2}x\big)^\frac{3}{2}}\\ \end{array}\\ \hline \end{array} $$

$$\begin{align} &=uv-\int v \ du\\ &=\big(\sqrt{2}x+1\big)\bigg(\frac{1}{6\sqrt{2}}\big(1+4\sqrt{2}x\big)^\frac{3}{2}\bigg)-\int \bigg(\frac{1}{6\sqrt{2}}\big(1+4\sqrt{2}x\big)^\frac{3}{2}\bigg)\big(\sqrt{2}\ dx\big)\\ &=\frac{1}{6\sqrt{2}}\big(\sqrt{2}x+1\big)\big(1+4\sqrt{2}x\big)^\frac{3}{2}-\frac{1}{6}\int \big(1+4\sqrt{2}x\big)^\frac{3}{2}\ dx\\ &=\frac{1}{6\sqrt{2}}\big(\sqrt{2}x+1\big)\big(1+4\sqrt{2}x\big)^\frac{3}{2}-\frac{1}{6}\int w^\frac{3}{2}\ \frac{dw}{4\sqrt{2}}\\ &=\frac{1}{6\sqrt{2}}\big(\sqrt{2}x+1\big)\big(1+4\sqrt{2}x\big)^\frac{3}{2}-\frac{1}{24\sqrt{2}}\int w^\frac{3}{2}\ dw\\ &=\frac{1}{6\sqrt{2}}\big(\sqrt{2}x+1\big)\big(1+4\sqrt{2}x\big)^\frac{3}{2}-\frac{1}{24\sqrt{2}}\times\frac{w^\frac{5}{2}}{\frac{5}{2}}\\ &=\frac{1}{6\sqrt{2}}\big(\sqrt{2}x+1\big)\big(1+4\sqrt{2}x\big)^\frac{3}{2}-\frac{2}{120\sqrt{2}}w^\frac{5}{2}\\ &=\frac{1}{6\sqrt{2}}\big(\sqrt{2}x+1\big)\big(1+4\sqrt{2}x\big)^\frac{3}{2}-\frac{1}{60\sqrt{2}}\big(1+4\sqrt{2}x\big)^\frac{5}{2}\\ &=\frac{1}{60\sqrt{2}}\big(1+4\sqrt{2}x\big)^\frac{3}{2}\big(10\big(\sqrt{2}x+1\big)-\big(1+4\sqrt{2}x\big)\big)\\ &=\frac{1}{60\sqrt{2}}\big(1+4\sqrt{2}x\big)^\frac{3}{2}\big(10\sqrt{2}x+10-1-4\sqrt{2}x\big)\\ &=\frac{1}{60\sqrt{2}}\big(1+4\sqrt{2}x\big)^\frac{3}{2}\big(6\sqrt{2}x+9\big)\\ \end{align}$$


Work: $$\begin{align} V&=\int_0^\sqrt{2}\pi\sqrt{x^2+3\sqrt{2}x-\big(\sqrt{2}x+1\big)\sqrt{1+4\sqrt{2}x}+1}^2 \ dx\\ &=\int_0^\sqrt{2}\pi x^2+3\pi \sqrt{2}x-\pi \big(\sqrt{2}x+1\big)\sqrt{1+4\sqrt{2}x}+\pi \ dx\\ &=\int_0^\sqrt{2}\pi x^2 \ dx+\int_0^\sqrt{2}3\pi \sqrt{2}x \ dx-\int_0^\sqrt{2}\pi \big(\sqrt{2}x+1\big)\sqrt{1+4\sqrt{2}x} \ dx+\int_0^\sqrt{2}\pi \ dx\\ &=\pi\int_0^\sqrt{2}x^2 \ dx+3\pi \sqrt{2}\int_0^\sqrt{2}x \ dx-\pi \color{red}{\int_0^\sqrt{2}\big(\sqrt{2}x+1\big)\sqrt{1+4\sqrt{2}x} \ dx}+\pi\int_0^\sqrt{2}dx\\ &=\pi\bigg[\frac{x^3}{3}\bigg]_0^\sqrt{2}+3\pi \sqrt{2} \bigg[\frac{x^2}{2}\bigg]_0^\sqrt{2}-\pi \bigg[\frac{1}{60\sqrt{2}}\big(1+4\sqrt{2}x\big)^\frac{3}{2}\big(6\sqrt{2}x+9\big)\bigg]_0^\sqrt{2}+\pi[x]_0^\sqrt{2}\\ &=\pi\bigg[\frac{2\sqrt{2}}{3}-\frac{0}{3}\bigg]+3\pi\sqrt{2}\bigg[\frac{2}{2}-\frac{0}{2}\bigg]-\pi\bigg[\frac{(9)^\frac{3}{2}(21)}{60\sqrt{2}}-\frac{(1)^\frac{3}{2}(9)}{60\sqrt{2}}\bigg]+\pi\big[\sqrt{2}-0\big]\\ &=\pi\bigg[\frac{2\sqrt{2}}{3}\bigg]+3\pi\sqrt{2}[1]-\pi\bigg[\frac{558}{60\sqrt{2}}\bigg]+\pi\big[\sqrt{2}\big]\\ &=\frac{2}{3}\pi\sqrt{2}+3\pi\sqrt{2}-\frac{93}{20}\pi\sqrt{2}+\pi\sqrt{2}\\ &=\pi\sqrt{2}\bigg(\frac{40}{60}+\frac{180}{60}-\frac{279}{60}+\frac{60}{60}\bigg)\\ &=\pi\sqrt{2}\bigg(\frac{1}{60}\bigg)\\ &=\frac{\pi\sqrt{2}}{60} \end{align}$$

Using the disk method, integrate $\pi r^2$ from $[0,\sqrt{2}]$ with Eqn. 8 plugged in for $r$ with respect to $x$.

TL;DR

Frankly, the question does not seem that complicated, and the answer of $\frac{\pi\sqrt{2}}{60}$ is definitely pretty simple. I have to believe that there is a more concise way of solving this problem.

All thoughts/answers welcome, thanks!

$\endgroup$
  • $\begingroup$ I don't want to sound discouraging, but this looks like more of an essay or an article than a question. $\endgroup$ – mathreadler Dec 17 '18 at 22:17
  • 1
    $\begingroup$ @mathreadler Not at all! Generally, I’ve been told on SE to show things that I have already tried. So I figure that, even though this is long, it helps people understand where I am and what I’m thinking. Maybe that’s just me... $\endgroup$ – Shady Puck Dec 17 '18 at 22:36
2
$\begingroup$

For $0 < x < 1,$ consider the line segment from $(x,x^2)$ to $(x,x).$ Rotated around the line $y = x,$ this produces a finite conical "hat" with slant height $x - x^2$ and base radius $(x - x^2)/\sqrt2,$ so it has surface area $\pi(x - x^2)^2/\sqrt2.$

The solid is composed of a nested stack of these conical "hats." The volume element between the "hat" at $x$ and the "hat" at $x + dx$ is $\frac\pi{\sqrt2}(x - x^2)^2 dx,$ so we integrate $$ \int_0^1 \frac\pi{\sqrt2}(x - x^2)^2 dx = \frac\pi{\sqrt2}\left[\frac{x^5}5 - \frac{x^4}2 + \frac{x^3}3\right]_0^1 = \frac{\pi\sqrt2}{60}. $$

$\endgroup$
  • $\begingroup$ I suppose if your starting point did not take into account just how amazing and robust the subject of Calculus is, you should put on a dunce cap! (+1) $\endgroup$ – CopyPasteIt Dec 19 '18 at 12:11
  • $\begingroup$ An incredibly simple and efficient method. Thank you very much! I just applied this method to the problem of the more general case ($y=ax^2$ rotated about $y=bx$). It made finding my final answer a breeze. +1 & accepted! One question: Do you mean the lateral area of the cone instead of the surface area? Because that's what your math seemed to say and what made more sense. $\endgroup$ – Shady Puck Jan 1 at 19:37
  • $\begingroup$ The lateral area is what I meant; another way to describe it is what is left after you remove the circular bottom surface area from a finite right circular cone. $\endgroup$ – David K Jan 1 at 20:16
1
$\begingroup$

Yes, using the disk method and you wind up having to contend with some unwieldy calculations. Use cylindrical shells to make your life easier. Here are some equations/algebra that will be needed:

The distance between the line $y = x + c$ and the line $y =x$ is equal to $\frac{|c|}{\sqrt 2}$.

If both $y = x + c$ and $y = x^2$ are true, then

$\tag 1 x^2 -x -c = 0$

Using the quadratic formula,

$$\tag 2 x_0 = \frac{1 - \sqrt{1 + 4c}}{2} \text{ and } x_1 = \frac{1 + \sqrt{1 + 4c}}{2} $$

The distance between $(x_0, x_0+c)$ and $(x_1, x_1+c)$ is given by $\sqrt {2}\,\sqrt {1+4c}$.

Letting $c$ vary, it ranges from $0$ to $-\frac{1}{4}$. Using a change of variable, set $u = -\frac{c}{\sqrt 2}$, so that

$\tag 3 u \text{ varies from } 0 \text{ to } \frac{\sqrt 2}{8}$

You are a few steps away from setting up your

$$\quad \int_{u=0}^{\frac{\sqrt 2}{8}} du$$

integral.

I worked it out using Wolfram and the volume is $0.074048\dots$, which is equal to $\frac{\pi\sqrt{2}}{60}$.

Integral Answer (use cursor as a 'spoiler'):

$$\quad 2 \pi \,\sqrt 2 \int_{u=0}^{\frac{\sqrt 2}{8}} u \sqrt{1 + 4\sqrt2 \,u} \;du$$

$\endgroup$
  • $\begingroup$ This is a great adaptation of the shell method! I found this very useful, and it helped confirm my equation for the general case, $y=ax^2$ rotated about $y=bx$. (+1) Truly a very clever procedure, except that I feel I have to accept the one by @DavidK based on its exceptional simplicity. Still, this was very helpful. Thank you very much! $\endgroup$ – Shady Puck Jan 1 at 19:41
  • 1
    $\begingroup$ @ShadyPuck And thank you for the question - the work that you put into it was an inspiration to look at it from other angles. $\endgroup$ – CopyPasteIt Jan 1 at 19:50
1
$\begingroup$

How about using the rotation matrix $\begin{pmatrix}\cos\frac{\pi}4&-\sin\frac{\pi}4\\\sin\frac{\pi}4&\cos\frac{\pi}4\end{pmatrix}$ to rotate $(x,y)$, and then you can integrate along $x$.

Then I get the equation $y^2+x^2-\sqrt2 x+\sqrt2 y+2xy=0$.

To solve for y we can use the quadratic formula: $y=\frac{-(2x+\sqrt2)\pm\sqrt{2+8\sqrt2 x}}2=\frac{-2x-\sqrt2\pm\sqrt2 \sqrt{1+4\sqrt2x}}2$.

So now we need to integrate. We need $\pi\int_0^{\sqrt2}y^2\operatorname dx$ and this can be done by integrating by parts, as you noted.

I used an integral calculator (too lazy) to check this and your answer appears to be correct.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.